Tensions between Religion and Policy: Navigating the Public Sphere - Usman Sambo (Religion and Policy Journal, 2023)
Research Problem: This abstract delves into the challenges posed by the integration of religion in state policy within multicultural societies. It highlights the tensions that arise when religious beliefs intersect with secular governance principles, and the dilemmas governments face in balancing religious freedom with the separation of religion and state.